Undefeated : Jim Thorpe and the Carlisle Indian School Football team - Sheinkin, Steve (Roaring Brook Press, 2017)
"A great American sport and Native American history come together in this true story of how Jim Thorpe and Pop Warner created the legendary Carlisle Indians football team"--